Struktur Dramatik Tari Wanka di Sanggar Sastra Mataya Banyuasin - Muhammad Alfaruqi; Rully Rochayati; Silo Siswanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Wanka dance is a new dance creation that was displayed at the blessing of the St. Maria Vianney, Pangkalpinang Diocese. This work is a visualization of the journey of contract laborers from China to Bangka to mine tin. This writing aims to describe the dramatic structure contained in Wanka’s dance work. Dramatic structure is an important part of a dance work. The existence of a dramatic stucture will make a dance work more interesting. The overlow of emotions to be conveyed can be presented in stages starting from the beginning, development, to the climax, then ending with completion so that the audience can also feel and be amazed by the dance work. This writing uses qualitative methods. The data in this writing were collected using observation, interview, and documentation methods, than processed and the results were written descriptively. The result of this writing is a description of the Wanka dance which is divided into four dance scences. Scence 1 is the beginning, scene 2 and scene 3 are the development of the conflict, scene 4 is the climax (peak of the conflict), and endes with a resolution.